1995
DOI: 10.1111/j.1365-246x.1995.tb03516.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on precessing flows in the Earth's liquid core

Abstract: S U M M A R YExperiments simulating flow in the Earth's liquid core induced by luni-solar precession of the solid mantle indicate, to a first approximation, that the core behaves like a rigidized fluid sphere spinning slower than the mantle and with its spin axis lagging the mantle spin axis in precession. Secondary flow patterns are always present. At low precession rates the fluid sphere is subdivided into a set of cylinders coaxial with the fluid spin axis, the cylinders rotating alternately at slightly fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
124
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(136 citation statements)
references
References 40 publications
(65 reference statements)
10
124
2
Order By: Relevance
“…The third type is by far the most accessible to theoretical analysis and is understood best. However, early experiments conveyed the intuition that the second type is the most important (Malkus 1968;Vanyo et al 1995). Clearly, different instabilities set in Fig. 14 Sketch of the structure of unstable precession driven flow (from Lorenzani and Tilgner 2001) first depending on the control parameters and we do not know at present what to expect for planetary values.…”
Section: Tidally Driven and Precession Driven Dynamosmentioning
confidence: 99%
“…The third type is by far the most accessible to theoretical analysis and is understood best. However, early experiments conveyed the intuition that the second type is the most important (Malkus 1968;Vanyo et al 1995). Clearly, different instabilities set in Fig. 14 Sketch of the structure of unstable precession driven flow (from Lorenzani and Tilgner 2001) first depending on the control parameters and we do not know at present what to expect for planetary values.…”
Section: Tidally Driven and Precession Driven Dynamosmentioning
confidence: 99%
“…It is estimated that there is abundant energy in rotation to sustain the generation of planetary magnetic fields [Kerswell, 1996]. It has been shown experimentally that the spatially complex flows required for dynamo action can occur in nonuniformly rotating spheroidal systems [Malkus, 1968;Vanyo et al, 2007;Noir and Cardin, 2001;Noir et al, 2003]. Recently, it has been convincingly demonstrated that precession-driven flows can indeed generate and sustain magnetic fields [Tilgner, 2005;Wu and Roberts, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Note that spheroidal or ellipsoidal geometry has frequently been employed by many authors to study fluid motion in geophysical and astrophysical contexts (see e.g. Vanyo et al 1995;Lorenzani & Tilgner 2001;Noir et al 2003;Wu & Roberts 2009;Le Bars et al 2010).…”
Section: Introduction and Formulationmentioning
confidence: 99%